Achievements, Gaps, and Emerging Challenges in Controlling Malaria in Ethiopia - Yalew, Amsalu Woldie (Frontiers in Tropical Diseases, 2022)
Malaria is one the major public health problems in Ethiopia, and thus controlling malaria is one of its top health sector priorities. The concrete interventions undertaken in past 20 years have resulted in a substantial decline in morbidity, and mortality attributable to malaria. Building on these past achievements, Ethiopia envisages to eliminate malaria by 2030. Realizing this ambition, however, needs to address some of the existing gaps, and emerging threats. Among others, Ethiopia needs to enhance its capacity in terms of malaria microscopy diagnosis, resource mobilization, vector surveillance, and seasonal weather forecasts.